What Happened in Cyprus? The Economic Consequences of the Last Communist Government in Europe - Athanasios Orphanides (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2014)
This paper reviews developments in the Cypriot economy following the introduction of the euro on 1 January 2008 and leading to the economic collapse of the island five years later. The main cause of the collapse is identi?ed with the election of a communist government in February 2008, within two months of the introduction of the euro, and its subsequent choices for action and inaction on economic policy matters. The government allowed a rapid deterioration of public finances, and despite repeated warnings, damaged the country's creditworthiness and lost market access in May 2011. The destruction of the island's largest power station in July 2011 subsequently threw the economy into recession. Together with the intensification of the euro area crisis in the summer and fall of 2011, these events weakened the banking system which was vulnerable due to its exposure in Greece. Rather than deal with its ?scal crisis, the government secured a loan from the Russian government that allowed it to postpone action until after the February 2013 election. Rather than protect the banking system, losses were imposed on banks and a campaign against them was coordinated and used as a platform by the communist party for the February 2013 election. The strategy succeeded in delaying resolution of the crisis and avoiding short-term political cost for the communist party before the election, but also in precipitating a catastrophe right after the election.
urn:nbn:de:hebis:30:3-343199
Keywords: D72; E32; E65; F34; H12; H63; 330; Cyprus; euro area; crisis; sovereign debt; populism.